Solve using the Square Root Property 12+(-6x)=30(-3)

Math
12+(-6x)=30(-3)
Multiply 30 by -3.
12-6x=-90
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Subtract 12 from both sides of the equation.
-6x=-90-12
Subtract 12 from -90.
-6x=-102
-6x=-102
Divide each term by -6 and simplify.
Tap for more steps…
Divide each term in -6x=-102 by -6.
-6x-6=-102-6
Cancel the common factor of -6.
Tap for more steps…
Cancel the common factor.
-6x-6=-102-6
Divide x by 1.
x=-102-6
x=-102-6
Divide -102 by -6.
x=17
x=17
Solve using the Square Root Property 12+(-6x)=30(-3)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top